Determining Intention to Visit Negeri Sembilan among Local Young Tourist in Malaysia - Hoo, Wong Chee; Ng, Alex Hou Hong; Chew, Livy; Ling, Zhu (Journal of Ecohumanism, 2024)
Many organisations will experience an effect on their target population as a result of demographic shifts. Therefore, in order to increase their market share and profitability, all companies must target a younger demographic. Malaysia’s greatest contributor to its gross domestic product is tourism, which takes advantage of the country’s numerous picturesque landscapes. Additionally, Seremban is a highly frequented tourist destination, attracting a significant number of visitors. This research demonstrates how the Malaysian tourism sector can effectively appeal to a younger demographic of tourists. This research endeavour will employ generation theory to examine the attributes of a locality that influence the visitation patterns of individuals within the 15–30 age bracket in Seremban. Once the data collection is complete, This study will employ the SmartPLS software for data analysis. The purpose of this analysis is to establish a statistically significant relationship between the dependent variable, Young Generation Tourism for Visiting Seremban, and the independent variables, Amenities, Attractions, Complementary Services, and Entrance Fees.